THE TRANSFORMATION OF PRIVATE VEHICLE USERS TO PUBLIC TRANSPORT USERS (CASE STUDY: BALI, INDONESIA) - Arnaya, I Wayan; Friman, Margareta; Munthohar, Imam (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
One of the roots traffic congestion is high number of private vehicle which triggered by an increase in the number of population. Switching users of private vehicle to public transport regarding to the affecting factor supposed to be examining first to solve traffic congestion. Based on factor analysis, there are two major factor on transport mode choice; quality (time, comfort, cleanness, safety, security, accessibility, and reliability ) and cost. Therefore, the government should be taking into considerations priority, which offer high contribution on solution made as priority. In order to achieving goal; the quality criteria reached contribution value that of 68% and 32% for cost criteria. Quality criteria compiled by time which has 61.8% of contribution value, safety (15.2%), accessibility (9.1%), security (8.8%), reliability (2.4%), comfort (1.7%), and cleanness as the priority within quality criteria has 1% of contribution. On the other dimension, cost criteria contain of fuel subsidy reached 95.664% of contribution, parking rate (3.947%), progressive tax (0.366%), and LCGC issue (0.023%).